Does Exposure to the Refugee Crisis Make Natives More Hostile? - HANGARTNER, DOMINIK; DINAS, ELIAS; MARBACH, MORITZ; MATAKOS, KONSTANTINOS; XEFTERIS, DIMITRIOS (The American political science review, 2019)
Although Europe has experienced unprecedented numbers of refugee arrivals in recent years, there exists almost no causal evidence regarding the impact of the refugee crisis on natives’ attitudes, policy preferences, and political engagement. We exploit a natural experiment in the Aegean Sea, where Greek islands close to the Turkish coast experienced a sudden and massive increase in refugee arrivals, while similar islands slightly farther away did not. Leveraging a targeted survey of 2,070 island residents and distance to Turkey as an instrument, we find that direct exposure to refugee arrivals induces sizable and lasting increases in natives’ hostility toward refugees, immigrants, and Muslim minorities; support for restrictive asylum and immigration policies; and political engagement to effect such exclusionary policies. Since refugees only passed through these islands, our findings challenge both standard economic and cultural explanations of anti-immigrant sentiment and show that mere exposure suffices in generating lasting increases in hostility.